American education - Spring, Joel H.
Clear, concise, and authoritative, American Education brings current issues and challenging perspectives to teacher educators' classrooms. Revised every two years, the text provides an up-to-date introduction to the historical, political, social, and legal foundations of education and to the profession of teaching in the United States